Activating amorphous Ru metallenes through Co integration for enhanced water electrolysis - Jose, Vishal (2023)
Designing efficient bifunctional electrocatalysts with excellent activity and robust stability presents a central challenge for the large-scale commercialization of water electrolysis. Herein, a facile approach is reported for the construct of atomically thin amorphous RuM (M-Co, Fe, or Ni) bimetallenes as high-performance electrocatalysts toward both electrochemical hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The RuCo bimetallene manifests excellent bifunctional activity characterized by low required overpotentials, superior price activity, robust electrochemical durability as well as a low cell potential water splitting performance, outperforming Pt/C and RuO2 benchmark catalysts. Combined operando X-ray absorption spectroscopy investigation and theoretical simulations reveal the synergism taking place between binary constituents, in which Co serves a promotive role along the HER/OER reaction pathway, contributing via optimal binding to *OH for facile water dissociation as well as modulating the Ru electronic structure favorably, hence rendering high activity catalytic centers for both the alkaline HER and OER.